Benefit sharing from whale shark tourism in Botubarani, Gorontalo and Labuhan Jambu, Teluk Saleh. Issue 1 (May 2021) - Djunaidi, A; Jompa, J; Nadiarti, N; Bahar, A; Tilahunga, S D
Abstract: Whale shark tourism is a growing industry in the world. This study aimed to determine the benefits local people earn from whale shark tourism at two sites in Indonesia, Botubarani in Gorontalo Province and Labuhan Jambu, Teluk Saleh, Nusa Tenggara Barat Province. This study involved dive centres, fishermen, community tourism groups, village enterprises (BUMDES), home stay owners, car rental companies, boat owners, lift net owners, snorkelling equipment rental businesses and ecotourism operators. In Botubarani, dive centres sold whale shark watching dive trips for US$42.3/pax, and snorkelling trips for US$23/pax, of which, US$4.6 and US$2.7 went to the Pokdarwis, and US$33.5 to the dive centre. For nondivers, trips cost US$11.5, of which US$1.5 was for whale shark bait, US$1.5 went to the Pokdarwis, and US$4.6 to fishermen. Whale shark watchers in Labuhan Jambu paid US$211.5-US$270 to ecotourism operators plus US$7.7/pax to the BUMDES. From that money, US$119 was paid to lift net owners, US$42 to boat operators, and US$19.2-US$76.9 to ecotourism operators. On average, car rental companies received US$46.1, home stays received US$7.6, and US$11.5 was paid for rental equipment.